c.3 - Joshi, J. M. (New Delhi, 1979)
The basic objective in writing this book is to provide a standard and up-to-date textbook on Microeconomic Theory for the postgraduate students of economics and commerce of Indian universities, as also for the candidates intending to appear at the higher competitive tests with economics as their major subject. The book, therefore, intends to cover all the courses included under "Micro economic Theory", "Theory of Price", "Price System and Resource Alloca tion", "Value and Distribution", "Welfare Economics" and similar other titles, prescribed in various Indian universities.
Keywords: Income distribution